The Impact of Training by Social Problem-Solving Model of D-Zurilla & Gold Fried on Problem-Solving Skills of Nursing Students - Shahbazi S; Heidari M (Iran University of Medical Sciences, 2012)
Background & Aim : Problem solving is a skill vital for life today and its learning is essential for everyone. Considering that the best way to achieve the correct habits of thinking and judgment is to use educational programs and to confront students with real issues, the aim of this study was to identify the effect of D' zurilla & gold fried problem solving model's training on problem solving skill of nursing students.   Materials & Methods: It was a randomized controlled trial. The sample consisted of 43 undergraduate nursing students of the Hazrat Ftemeh School of nursing and midwifery of Shiraz University of Medical Sciences who participated voluntary and were randomly assigned into experimental(n= 20) and control (n=23) groups. The experimental group participated in six sessions of problem solving. Data was collected by the problem solving subscale of Bar-On emotional intelligence questionnaire and analyzed using SPSS-PC (v.11).   Results : there was a significant difference between the mean scores of problem solving skills in the experimental group and control group immediately and two months after the intervention (p<0.01).   Discussion : Regarding the impact of this model on the improvement of problem solving skills and the stability of its effects, using this model in different areas of nursing, including education, management, research and clinical area is recommended.